Answer:
1.
-2 = x/4 + 1
Subtract 1 from both sides:
-2 - 1 = x/4 + 1 - 1
-3 = x/4
Multiply both sides by 4:
-3 * 4 = x/4 * 4
-12 = x
2.
3x+5
3.
X= 12 or 18
This could be read two different ways.
0=2/3x-12
12=2/3x
12÷2/3=x
12*3/2=x
18=x
—-OR—-
0=2/3(x-12)
0=2/3x-8
8=2/3x
8÷2/3=x
8*3/2=x
12=x
The surface area would be 166.
Answer:
(x+2)(3x+1)
Step-by-step explanation:
Given at you have an equilateral triangle, all sides have the same length.
Therefore,
First side 2x-7 = Second side x+y-9 = Third side y+5
Let us look at the second and third sides for now:
x+y-9 = y+5
x = y+5 - (y-9)
x = y-y+5+9
x = 14
Then we look at equating the first and third sides:
2x-7 = y+5
y = 2x-7-5
Substitute x =14 in the equation above:
y = 2(14)-7-5
= 28-7-5
= 21-5
= 16
The length of the third side is:
y+5 = 16 +5 = 21
Given that the length of each sides are the same in an equilateral triangle, all sides have the length 21cm.
Answer:
B. slope
Step-by-step explanation: